VIRAL INFECTIONS AND THEIR IMPACT ON IMMUNE SYSTEM: A FOCUS ON INFECTIOUS MONONUCLEOSIS - Kamoldinov Marufjon (European Science Publishing, 2025)
This article explores the relationship between viral infections and the immune system, with a particular focus on infectious mononucleosis (IM), commonly known as "mono." The paper examines the pathophysiology of viral infections, how they interact with immune responses, and the specific impact of the Epstein-Barr virus (EBV), which is the primary causative agent of IM. Key aspects covered include the clinical manifestations, diagnostic methods, and the immune system's response to EBV infection. The article also discusses the potential complications of infectious mononucleosis, its effect on immune function, and how chronic or recurrent infections may influence long-term immune health. Finally, it reviews current treatment options and strategies for managing IM, as well as the importance of preventive measures in minimizing the spread of the virus.
Keywords: Viral infections, Immune system, Infectious mononucleosis, Epstein-Barr virus, Clinical manifestations, Diagnostic methods, Immune response, Complications, Treatment options, Prevention.